BRIDGE cross-scale approaches for water efficiency andclimate adaptation in Senegal - Vadez, Vincent (2024)
Presentation during the Science Policy dialogue on Crop diversification and water efficient pathways that took place 27-28 November 2024 in Saly, Senegal. Research showed that doubling of sowing density and water conservation techniques enable grain and biomass yield increase of dryland cereal in water stressed conditions; that upland rice can produce more grain per drop and its potential has been mapped in Casamance. Crop residue transformation could create new local animal feed value chains to increase feed security, a priority for Senegal. Participants recognised the priority to address the gap in fodder resources, as well as small scale mechanisation solution as labor shortage is an issue for both cropping systems. Finally, local level action research model involving farmers as carried out by BRIDGE teams has been found promising in term of knowledge co-production and impact.